Block-based variations in the impact of characteristics of urban functional zones on the urban heat island effect: A case study of Beijing. (January 2022) - Zhang, Nanyu; Zhang, Jianjun; Chen, Wei; Su, Jiajia
Highlights: The POI data could be used to identify buildings efficiently and conveniently. Building type is the manifestation of its characteristics and distribution. The degree of LST's response to building features varies by building type. The correlation between building features and LST is spatially non-stationary. Abstract: The spatial aggregation of buildings intensifies the urban heat island (UHI) effect and hinders the sustainability of a city. This study divided more than 200, 000 buildings in Beijing's Fifth Ring Road area into four categories, and used geographically weighted regression (GWR) to study the spatial heterogeneity of the impact of building features on land surface temperature (LST). The results showed that: (1) building characteristics are an essential factor affecting LST. Though the overall significance level was high, the correlation coefficient was within −0.3 and 0.4; (2) the correlation was spatially nonstationary. The R -squared value of GWR was approximately 0.4 higher than that of ordinary least squares (OLS). Although the body shape coefficient and LST were negatively correlated, the relationship between the low-rise building clusters was positive. In addition, the building height of blocks with a low building density was positively correlated with LST; (3) there were differences in the strength of between building types. Residential buildings had the strongest correlation, and commercial buildings had the weakest. This study provides a reference for planners to adjust the layout of block buildings and reduce the UHI effect.